2011
DOI: 10.1111/j.1439-0396.2009.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of starch gelatinisation degree on intestinal morphology, intestinal pH and bacteriology in pigeons

Abstract: The effect of starch gelatinisation degree in extruded feed on intestinal morphology, intestinal pH and faecal bacteriology was investigated in pigeons. Extruded complete pigeon diets would offer the principle advantage of providing equilibrated nutrients and energy, but factors such as starch gelatinisation require investigation before these diets are offered as main dietary items to pigeons. Birds were fed two diets with equal ingredient composition and nutrient content, but with a different degree of starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Diet may influence animal urine pH (Burton 1980) and also the nitrate content in pigeon excreta (Sales & Janssens 2003a, 2003b. Experimental studies found that pigeon diets with a high gelatinisation of the constituent starches (i.e., cooking) resulted in excreta with a higher pH than an identical diet modified to have a lower gelatinisation (Abd El- Khalek et al 2011). While this study is in- dicative only, as the differences were not statistically significant, it nonetheless suggests that processed foods (cooked human discards) may induce a higher pH than unprocessed, natural diets, such as grass seeds.…”
Section: Factors Influencing the Acidity Of Ex-cretamentioning
confidence: 99%
“…Diet may influence animal urine pH (Burton 1980) and also the nitrate content in pigeon excreta (Sales & Janssens 2003a, 2003b. Experimental studies found that pigeon diets with a high gelatinisation of the constituent starches (i.e., cooking) resulted in excreta with a higher pH than an identical diet modified to have a lower gelatinisation (Abd El- Khalek et al 2011). While this study is in- dicative only, as the differences were not statistically significant, it nonetheless suggests that processed foods (cooked human discards) may induce a higher pH than unprocessed, natural diets, such as grass seeds.…”
Section: Factors Influencing the Acidity Of Ex-cretamentioning
confidence: 99%
“…Recently, crude ash digestibility-as a measure of mineral absorption-showed a considerable increase due to decreasing the degree of starch gelatinisation of a complete extruded diet for pigeons [18]. A consecutive trial indicated that intestinal pH and changes in intestinal morphology might attribute to this phenomenon [19]. Therefore, the impact of trace element sources might depend on the composition and processing of the basal diet, which urges-as a next step-for an evaluation of trace element sources in different diets.…”
Section: Discussionmentioning
confidence: 96%
“…This process of extrusion creates starch gelatinization but also Maillard products and fat hydrogenation among other things. A recent study showed that lower degree of starch gelatinization in extruded diets enhance digestibility in pigeons (Abd El‐Khalek et al., ). Maillard products reduce the availability of amino acids, and fat hydrogenation leads to high level of fatty acids, which could increase the risk of atherosclerosis.…”
Section: Veterinarian Perspectivesmentioning
confidence: 99%